The 2010 Fifa world cup: Perceptions of its sports and development legacy potential - Mills, Lucy Caroline (Department of Sociology, 2014)
Sport mega-events are a contemporary phenomenon which embody and unify global processes in an increasingly globalised world. Whilst the sport industry has grown exponentially as a result of global market forces envisaging extensive economic opportunities, hosting a mega-event has also been economically attractive for cities and countries. In aiming to be globally competitive and world-class, mega-events derive from an economic-growth centred model of urban development, whereby benefits will 'trickle-down' to the poor and marginalised (Pillay and Bass, 2008). The 2010 FIFA World Cup typifies such an event as it encompasses historical, geopolitical, economic and socio-cultural processes that have intensified and been intensified by, globalisation. South Africa's bid for the 2010 FIFA World Cup however, has differed from other mega-event bids. Official World Cup discourses boast that the World Cup will produce lasting socio-economic impacts to South Africa and indeed the rest of Africa. FIFA and the South African government have labelled the 2010 World Cup an 'African World Cup' with promises of stimulating pan-African economic and sociocultural opportunities. There is significant emphasis on providing social benefits to underprivileged populations. One of the anticipated social legacies is the development of sport structures and increased participation of sport in disadvantaged areas where barriers to sport are most entrenched. The aim of the research project was to determine whether a sport and development legacy is in fact materialising in both South Africa and Zambia as a result of South Africa hosting the World Cup. I employed a qualitative research design and conducted 20 semi-structured in-depth interviews with representatives from a wide variety of sport and development related organisations in Cape Town and Lusaka. I regarded this cross-section of people as best positioned to provide evidence of a legacy. v Findings demonstrate that the official World Cup discourses generated by FIFA and the South African government pledging benefits continent-wide, have infiltrated everyday discourse of people in townships in Lusaka and Cape Town. There is however a discrepancy between this rhetoric and the reality. Respondents from smallscale, community-based sports structures rarely perceive themselves or their organisations to benefit from World Cup opportunities due to a lack of access to information and resources. Despite limited tangible gains or involvement, a sense of pride in South Africa, and indeed Africa, is evident. This alone is contributing to the support of the World Cup rather than visible positive changes in disadvantaged communities. In contrast to these organisations, representatives from larger, wealthier sport for development NGOs record increased funding and activities. This research has therefore exposed a dual system of sports delivery present in South Africa and Zambia. Whilst sport for development NGOs thrive, community sports structures struggle to the point of being near dysfunctional or even non-existent. Given the problematic history of donor-driven, Northern-based development programmes, we must be wary of perpetuating the marginalisation of local voices. This thesis suggests that pitfalls of globalisation at large are reproduced in globalised sport. It substantiates existing literature that doubts the potential of the World Cup to generate development among poorer populations.